Does Aristotle dialogue with Parmenides? - Cárdenas Mejía, Luz Gloria (Estudios de Filosofía, 1998)
The question about the role of repeated references to the opinions of his predecessors and contemporaries has regained a great importance in nowadays Aristotelian studies. Based on Hans-Georg Gadamer's statement that such references mean a living dialogue between the philosopher and his predecessors, the author shows that in the case ofthe dialogue with Parmenides that living character is rooted in the rhetoric and dialectical procedures he employs.